2019
DOI: 10.1093/nar/gkz867
|View full text |Cite
|
Sign up to set email alerts
|

VISDB: a manually curated database of viral integration sites in the human genome

Abstract: Virus integration into the human genome occurs frequently and represents a key driving event in human disease. Many studies have reported viral integration sites (VISs) proximal to structural or functional regions of the human genome. Here, we systematically collected and manually curated all VISs reported in the literature and publicly available data resources to construct the Viral Integration Site DataBase (VISDB, https://bioinfo.uth.edu/VISDB). Genomic information including target genes, nearby genes, near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 37 publications
5
44
0
Order By: Relevance
“…Whether this might represent one of several components for risk stratification remains to be determined. Our results, together with a recent study [58], have shown that viral integrations may also occur in other genetic elements that are involved in regulation of gene expression, such as ncRNA and UTRs. and HPV18 are to a certain degree associated with different types of invasive cervical cancers [3,4] and may utilise different molecular mechanisms to induce carcinogenesis.…”
Section: Discussionsupporting
confidence: 78%
“…Whether this might represent one of several components for risk stratification remains to be determined. Our results, together with a recent study [58], have shown that viral integrations may also occur in other genetic elements that are involved in regulation of gene expression, such as ncRNA and UTRs. and HPV18 are to a certain degree associated with different types of invasive cervical cancers [3,4] and may utilise different molecular mechanisms to induce carcinogenesis.…”
Section: Discussionsupporting
confidence: 78%
“…The major sources of data in ViMIC were derived from abundant published literatures, the Cistrome Data Browser (18,19), VISDB (21) and GEO database (20). Viral annotation information was retrieved from a large collection of published literature through our text-mining system, which was followed by a manual curation process.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Therefore, it is quite challenging for researchers to quickly search, visualize, and re-use such knowledge for their studies of virus-host interactions. Several databases, such as the Viral Integration Site DataBase (VISDB) (21), Dr.VIS (22), the Retrovirus Integration Database (RID) (23) and the ISDB (24) have been developed. However, to our knowledge, these databases focused on virus integration, and none of existing databases or web-servers are designed for systematically evaluating VMs and functionally annotating of VISs.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary of DeepHBV to be applied on general datasets, we tested the pre-trained DeepHBV models (DeepHBV with HBV integration sequences + repeat peaks and DeepHBV with HBV integration sequences + TCGA Pan Cancer peaks) on the HBV integration sites dataset in another viruses integration sites (VIS) database VISDB [19]. We found that in the model trained with HBV integration sequences + repeat sequences showed an AUROC of 0.6657 and an AUPR of 0.5737, while the model trained with HBV integrated sequences + TCGA Pan Cancer showed an AUROC of 0.7603 and an AUPR of 0.6189.…”
Section: Resultsmentioning
confidence: 99%